الهدي النبوي في الطيب - Rohaizan, Baru; Islam Hassan, Mohammad Yaseen (2016)
This study discusses the prophet’s method of using perfume. This is to show that Islam considers the perfume important in the life of mankind, so as to encourage Muslims to use fragrance. It is observed that many Muslims do not consider perfume important. This study explains the role of Islam in taking care of the Muslims’ beauty with regard to perfume. The researchers employed analytical approach to collect data from Hadith books, explain, examine and extract meaning. The study explains the meaning of perfume, how the prophet (peace be upon him) considers it important, and when and where it is needed, as well as when and where it is prohibited. The study revealed that the Prophet (peace be upon him) encourages the use of perfume, and by adhering to this Sunnah (prophetic tradition), a Muslim can achieve good here and hereafter, and become more pleasant. One the other hand, by adhering to the Sunnah of the Prophet, one can go closer to the Almighty Allah.